DESENVOLVIMENTO, OTIMIZAÇÃO E VALIDAÇÃO DE METODOLOGIA ELETROANALÍTICA PARA A DETERMINAÇÃO DE 2,4,6 - TRICLOROFENOL EM ÁGUAS E ALIMENTOS - Schwab, Emanuele Dal Pisol (2017)
The development, optimization and validation study of electrochemical methodologie for 2,4,6 – trichlorophenol (2,4,6 – TCP) determination in natural water and food is reported in this work. The determination of 2,4,6 – tricholorophenol (2,4,6 – TCP) in real samples by ciclic voltametric (CV) and square wave voltametry (SWV) using a boron-doped diamond electrode (BDD) is described. Measurements carried out in solution of the Britton-Robbinson buffer with pH = 8,0 revealed a single oxidation peak at 0,72 V vs Ag/AgCl for 2,4,6 – TCF in a process that is controlled by the difusuin of the species on the electrode surface. After sistem optimization, a validation study was performed and such as linearity, limits of detection (LD) and quantification (LQ), precision, accuracy and seletivity were evaluated applying different statistical tests to confirm the reliability of the development method. Analytical curve obtained with standart addiction was employed for the pesticide analyzed, where it showed good linearity in the investigated concentration range, with values of Fregression >> Fcritical and no lack off fit of linear model was observed.The limits of detection (LD) and quantification (LQ) obtained were 2,05x10-8 mol L-1 and 6,82x10-8 mol L-1 respectively. The recoveries were adequated and vary between 90% and 118% for the natural water and food, indicating that the direct analysis presents adequate accuracy. The relative standard deviation obtained in the precision tests were lower than recommended by ANVISA E AOAC, (RSD (%) < 1,57). Thus, it is suggested that this metodology can be applied in the 2,4,6 – tricholorophenol determination with advantages over tradicional methods, as speed, low cost and reduction of reagent use.